Composition structure and size distribution of two mahseer species in the Sikundur River, Leuser Ecosystem Area, Aceh, Indonesia - Yusrizal Akmal; Muchammad Yunus; Hani Plumeriastuti; Yeni Dhamayanti; Irfannur Irfannur; Muliari Muliari; Agung Setia Batubara (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2025)
The fish diversity within the Leuser Ecosystem Area (LEA), particularly in the Sikundur River, plays a crucial role in maintaining the balance of freshwater ecosystems. However, the populations of Mahseer (Tor tambroides and Neolissochilus soro) in this region are under threat due to habitat alteration and intensive exploitation. This study aims to examine the composition structure and size distribution of these two Mahseer species in the Sikundur River. Data collection was conducted at three stations representing different ecological settings: a residential area (Station 1), an agricultural plantation (Station 2), and a natural forest (Station 3). The study was carried out across two seasonal periods, dry season (April–September 2023) and rainy season (October–March 2024). Fish were sampled using cast nets, gillnets, and handlines with the assistance of local fishers, during both morning and evening sessions. Samples were analyzed descriptively and presented in tables and graphs. Results showed that Station 3, located in a natural forest, had the highest proportion of juvenile and adult Mahseer with the largest sizes and weights, particularly during the dry season. Station 1 was dominated by smaller juveniles, especially in the rainy season. Station 2 displayed variable patterns. Seasonal and ecological differences significantly influenced Mahseer population structure and growth dynamics.